2008
DOI: 10.1007/s11270-008-9862-1
|View full text |Cite
|
Sign up to set email alerts
|

Relating Tree Ring Chemistry of Pinus densiflora to Precipitation Acidity in an Industrial Area of South Korea

Abstract: To test the possible use of tree ring chemical properties as proxies for precipitation acidity ([H + ]), we investigated the relationships between tree ring chemistry (δ 13 C, δ 15 N, Ca-to-Al ratio, and N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
7
23
1
Order By: Relevance
“…(Koopmans et al 1996;Schleppi et al 1999;Hart and Classen 2003;Balster et al 2009). In cases where tree ring [N] appears to reflect pollution inputs (Kwak et al 2009;Leonelli et al 2012), the response is inconsistent (Saurer et al 2004;Kwak et al 2011) or also documented in trees not exposed to pollution (Guerrieri et al 2009). …”
Section: The Role Of [N]mentioning
confidence: 99%
See 3 more Smart Citations
“…(Koopmans et al 1996;Schleppi et al 1999;Hart and Classen 2003;Balster et al 2009). In cases where tree ring [N] appears to reflect pollution inputs (Kwak et al 2009;Leonelli et al 2012), the response is inconsistent (Saurer et al 2004;Kwak et al 2011) or also documented in trees not exposed to pollution (Guerrieri et al 2009). …”
Section: The Role Of [N]mentioning
confidence: 99%
“…In fact, studies have shown N mobility throughout all plant tissues over the course of numerous growing seasons, indicating that N redistribution is a continual process (Mead and Preston 1994) (Elhani et al 2003;Kwak et al 2009). Under high pollutant inputs, the amount of extracted N was higher in recent rings, suggesting that increases in [N] in recent rings reflect increases in mobile N as opposed to structural N components (Doucet et al 2010).…”
Section: To Extract or Not Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…[CO2]) in the year when the specific growth ring was formed (Choi et al, 2005;Bukata andKyser, 2007, Choi et al, 2007;Kwak et al, 2009b C from fossil fuels at the global scale (Freyer and Belacy, 1983;February and Stock, 1999). Such inter-correlation may result in a negative relationship between atmospheric [CO2] and tree ring δ 13 C; i.e., a decrease in δ…”
Section: Introductionmentioning
confidence: 99%